Efficient bidirectional piezo-optomechanical transduction between microwave and optical frequency - Wentao Jiang (Nature Portfolio, 2020)
Current optomechanical implementations of microwave and optical frequency interconversion are lacking in efficiency and interaction strength. The authors design and demonstrate an on-chip piezo-optomechanical solution which overcomes several technical barriers to reach several orders of magnitude improvement in efficiency.